2013
DOI: 10.1111/prd.12007
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease and systemic illness: will the evidence ever be enough?

Abstract: The concept of focal infection or systemic disease arising from infection of the teeth was generally accepted until the mid-20th century when it was dismissed because of lack of evidence. Subsequently, a largely silo approach was taken by the dental and medical professions. Over the past 20 years, however, a plethora of epidemiological, mechanistic and treatment studies have highlighted that this silo approach to oral and systemic diseases can no longer be sustained. While a number of systemic diseases have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
157
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(163 citation statements)
references
References 168 publications
1
157
0
5
Order By: Relevance
“…Pathogens can cause a remote pathogenic effect by direct action via bacteriemia and by inducing production of several circulating cytokines (37). Increased levels of circulating cytokines, caused by periodontal disease, can trigger C-reactive protein production in the liver (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogens can cause a remote pathogenic effect by direct action via bacteriemia and by inducing production of several circulating cytokines (37). Increased levels of circulating cytokines, caused by periodontal disease, can trigger C-reactive protein production in the liver (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The major obstacles are the demands of a very large sample size of screen-detected subjects with periodontitis followed for a long time, probably in the magnitude of decades. 29 Moreover, it may be considered unethical to deny people with established dental disease treatment. A study design that could provide useful information on associations between various risk markers and myocardial infarction would be a carefully conducted case-control study as, for example, demonstrated over the years by the Stockholm Heart Epidemiology Program (SHEEP) a population-based case-referent study of causes of a first myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal infection and inflammation are known to affect systemic health and are associated with diseases such as cardiovascular disease and diabetes mellitus (2)(3)(4). Although periodontal infection is polymicrobial, Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia are known as representative periodontopathic bacteria and are called the red complex bacteria (RCB) (5).…”
mentioning
confidence: 99%